Aan duiding van Zen-trekke by Breyten Breytenbach - Steenberg, D. H. (Koers, 1985)
The author undertakes his analysis on the basis of his statement that he found it impossible to read Breytenbach without recourse to Zen-Buddhism. He deals briefly with the issue of the topicality of Zen-Buddhism. He analyses certain poems to point out the Zen-Buddhist experiential context and approach to reality before going on to a discussion of what constitutes Zen-Buddhism. The method of Zen-Buddhism, a looking into the self, a meditation, leads ultimately to a strongly ascetic lifestyle, and this spiritual discipline becomes determining for one's experience and life. He gives a diagrammatic representation of the implications of self-analysis in the Zen framework before analysing Breytenbach's poetry to indicate motifs and steps in the process. The analyses involve the theory of knowledge, the way to nirvana, the concepts of time and eternity and mysticism, a true acceptance of reality, the oneness of all things (including the "I", the awareness of mortality, death, the worldly, and in a long final section, the fallibility of language. The final conclusion is that the poetry in the relevant volumes demands a great deal of co-creative activity on the part of the reader. While Biblical and Zennist allusions converge, it emerges that Biblical referencesare merely communicative devices within a framework of over-arching Zen-Buddhist thought.